AGN Feedback and Its Quenching Efficiency - Combes, Francoise (Frontiers in Astronomy and Space Sciences, 2017)
In the last decade, observations have accumulated on gas outflows in galaxies, and in particular massive molecular ones. The mass outflow rate is estimated between 1-5 times the star formation rate. For the highest maximal velocities, they are driven by AGN; these outflows are therefore a clear way to moderate or suppress star formation. Some of the most convincing examples at low redshift come from the radio mode, when the radio jets are inclined towards the galaxy plane, or expand in the hot intra-cluster medium, in cool core clusters. However, AGN feedback can also be positive in many occasions, and the net effect is difficult to evaluate. The quenching efficiency is discussed in view of recent observations.